Influence of micropatterned substrates on keratocyte phenotype - Ahearne, Mark (My University, 2020)
Substrate topographic patterning is a powerful tool that can be used to manipulate cell shape and orientation. To gain a better understanding of the relationship between surface topography and keratocyte behavior, surface patterns consisting of linear aligned or orthogonally aligned microchannels were used. Photolithography and polymer molding techniques were used to fabricate micropatterns on the surface of polydimethylsiloxane (PDMS). Cells on linear aligned substrates were elongated and aligned in the channel direction, while cells on orthogonal substrates had a more spread morphology. Both linear and orthogonal topographies induced chromatin condensation and resulted in higher expressions of keratocyte specific genes and sulfated glycosaminoglycans (sGAG), compared with non-patterned substrates. However, despite differences in cell morphology and focal adhesions, many genes associated with a native keratocyte phenotype, such as keratocan and ALDH3A1, remain unchanged on the different patterned substrates. This information could be used to optimize substrates for keratocyte culture and to develop scaffolds for corneal regeneration.
PUBLISHED
Keywords: Surface topography; Keratocyte behavior; Surface of polydimethylsiloxane (PDMS); Polymer molding techniques; Photolithography; Patterns